Efficient nuclease-directed integration of lentivirus vectors into the human ribosomal DNA locus - Schenkwein, Diana; Afzal, Saira; Nousiainen, Alisa; Schmidt, Manfred; Ylä-Herttuala, Seppo (Molecular therapy, 2020)
Lentivirus vectors (LVs) are efficient tools for gene transfer, but the non-specific nature of transgene integration by the viral integration machinery carries an inherent risk for genotoxicity. We modified the integration machinery of LVs and harnessed the cellular DNA double-strand break repair machinery to integrate transgenes into ribosomal DNA, a promising genomic safe-harbor site for transgenes. LVs carrying modified I-PpoI-derived homing endonuclease proteins were characterized in detail, and we found that at least 21% of all integration sites localized to ribosomal DNA when LV transduction was coupled to target DNA cleavage. In addition to the primary sequence recognized by the endonuclease, integration was also enriched in chromatin domains topologically associated with nucleoli, which contain the targeted ribosome RNA genes. Targeting of this highly repetitive region for integration was not associated with detectable DNA deletions or negative impacts on cell health in transduced primary human T cells. The modified LVs characterized here have an overall lower risk for insertional mutagenesis than regular LVs and can thus improve the safety of gene and cellular therapy.